2011
DOI: 10.1007/s10646-011-0689-y
|View full text |Cite
|
Sign up to set email alerts
|

Traits and stress: keys to identify community effects of low levels of toxicants in test systems

Abstract: Community effects of low toxicant concentrations are obscured by a multitude of confounding factors. To resolve this issue for community test systems, we propose a trait-based approach to detect toxic effects. An experiment with outdoor stream mesocosms was established 2-years before contamination to allow the development of biotic interactions within the community. Following pulse contamination with the insecticide thiacloprid, communities were monitored for additional 2 years to observe long-term effects. Ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 123 publications
(88 citation statements)
references
References 56 publications
3
83
1
1
Order By: Relevance
“…Guidance for the evaluation of concentration-response relationships of populations and communities statistically (using, for example, multivariate analysis) and ecologically (using, for example, traits (e.g. Liess and Beketov, 2011) can be found the AGD (EFSA PPR Panel, 2013, section 9.3.2.5). Guidance for interpretation of concentration-response relationships by means of effect classes can be found in section 9.3.5.3 of the AGD (EFSA PPR Panel, 2013).…”
Section: Evaluating Effects and Interpreting Resultsmentioning
confidence: 99%
“…Guidance for the evaluation of concentration-response relationships of populations and communities statistically (using, for example, multivariate analysis) and ecologically (using, for example, traits (e.g. Liess and Beketov, 2011) can be found the AGD (EFSA PPR Panel, 2013, section 9.3.2.5). Guidance for interpretation of concentration-response relationships by means of effect classes can be found in section 9.3.5.3 of the AGD (EFSA PPR Panel, 2013).…”
Section: Evaluating Effects and Interpreting Resultsmentioning
confidence: 99%
“…Such indicators are a) organisms at the species and/or community level including functional groups such as earthworms (Bouché 1977), trophic groups such as nematodes (Yeates 2003) or trait groups such as aquatic invertebrates (Liess and Beketov 2011); b) direct functional endpoints such as litter decomposition, biogeochemical cycles completion; c) indirect functional endpoints such as ecological functions provided by single species or communities (Hilbeck 2008a, b;Schmitt-Jansen et al 2008) and ecosystem services such as biodiversity and habitat provision and/or pollinators securing food crop production (Faber and van Wensem 2012;Mace et al 2012); and d) landscape-scale related indicators such as land use diversity which may be affected by altered rotation and other production schemes (Graef 2009). They must represent not only arable areas, but neighbouring receiving environments including wild habitats, where the GM crops may have a potential impact or could occur.…”
Section: Indicators and Sampling Methods (Tc1)mentioning
confidence: 99%
“…This approach was adopted to study the effects of toxic contamination on invertebrate communities in running waters [15][16][17]. It was shown that tolerant taxa are characterized by resistance and resilience traits [e.g., high mobility (which permits avoidance of exposition and dispersion) and short life cycles (which allow rapid re-colonization after disturbance)].…”
Section: Community Functioning: Species Traitsmentioning
confidence: 99%
“…Riverine invertebrate communities have been extensively studied in response to gradients of contamination, producing effective toxicity indices [15][16][17]. By contrast, benthic communities in lakes have still been rather neglected, since the ecological status of lentic ecosystems has for long been assessed on the basis of only chemical and physical parameters.…”
Section: Introductionmentioning
confidence: 99%